Evaluation of motor development and effect of physical therapy intervention in surgical newborns in a Neonatal Intensive Care Unit (Fisioterapia e Pesquisa, 2022)
The objective of this study was verify the applicability of the Test of Infant Motor Performance (TIMP) in surgical newborns as a tool for evaluating motor performance and to evaluate the benefit of the physical therapy intervention. Surgical newborns, divided between group without physiotherapy (n=38) and group with motor physical therapy (n=38), were evaluated by TIMP and reevaluated 2 weeks later. The physiotherapy group performed standardized exercises for motor sensory stimulation once a day, while the no physiotherapy group received the usual care from the Neonatal Intensive Care Unit. The predominant surgical diagnosis in both groups was gastroschisis, followed by congenital diaphragmatic hernia. In the initial evaluation there was no difference in motor performance between the groups, classified as "below average" for age, with score -z = -1.28 (p=0.992). In the reassessment, the physiotherapy group presented better scores (p<0.001) and a higher difference in -z-score (p<0.001), higher percentage of newborns classified as "within the mean" (44% in the physiotherapy group and 2.6% in the no physiotherapy group), as well as a higher percentage of weight gain (p=0.038). In the revaluation there was a worsening of motor performance in 10.5% of the no physiotherapy group (p<0.001). Improvement in motor performance was observed in 81.6% of the physiotherapy group and in only 13.2% of the no physiotherapy group (p<0.001). Conclusion: TIMP was applied to newborns safely and effectively and needs to be performed by professionals experienced in the approach of this population. Motor intervention was beneficial, with significant improvement in motor performance, and if started early, it may be able to adapt the motor development of these newborns, even before hospital discharge.